Long-term outcome at age 7–10 years after extreme prematurity – a prospective, two centre cohort study of children born before 25 completed weeks of gestation (1999–2003). (13th January 2014) - Herber-Jonat, Susanne; Streiftau, Silke; Knauss, Eva; Voigt, Friedrich; Flemmer, Andreas W.; Hummler, Helmut D.; Schulze, Andreas; Bode, Harald
Abstract: Objective : We aimed to determine the long-term neurodevelopmental outcome in extremely preterm infants of 22–23 completed weeks' gestation as compared to infants of 24 weeks with immediate postnatal life support born in two German tertiary perinatal centres between 1999 and 2003. Methods : Children were assessed for cognitive and neurological outcomes at the age of 7–10 years. The test battery included a neurological examination, the Wechsler Intelligence Scale for children (WISC-IV) and the Frostigs Developmental Test of Visual Perception (DTVP-2). Gross motor function was classified according to the GMFCS and functional activity was assessed with the Lincoln Oseretzky Motor Development Scale (LOS KF 18). Results : Outcome data were available for 79/105 children. 75.9% of the entire study cohort showed no or mild impairment. There was no difference seen between the two gestational age groups. Risk factors for moderate or severe impairment were an intracerebral haemorrhage >II° and/or periventricular leukomalacia or a retinopathy of prematurity >II°. Neither the gestational age (GA) nor the birth weight was associated with long-term outcome. Conclusions : Gestational age was not a predictor for long-term impairment of preterm infants born <25 completed weeks' GA. Other prognostic factors should be taken into account for counselling in the grey zone of viability.